2023
DOI: 10.37311/jsscr.v5i1.17046
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Pengelolaan Obat di Puskesmas X Provinsi Kalimantan Selatan

Nida Anisah,
Sendi Lia Yunita,
Ika Ratna Hidayati

Abstract: Drug is an important aspect that needs to be considered in health services. Proper drug management is needed so that the availability of drugs is guaranteed and the quality of drugs is maintained. The purpose of this study was to determine drug management which includes planning, requesting, receiving and storing drugs at X Health care Center. This research is a quantitative research with a descriptive observational research design, using secondary data sources LPLPO and RKO as well as primary data sources by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Study at Tegal PHCs, reported that drug storage according to dosage form, temperature, and FEFO (First In, First Out) met the standard 100% (Cholilah et al, 2021). The percentage of the suitability of drug storage LASA (Look Alike Sound Alike) at Boja, Kendal PHCs was 50% (Yuswantina et al, 2022), Tegal PHCs was 87.5% (Cholilah et al, 2021) and South Kalimantan PHCs was 88% (Anisah et al, 2023). It was different at Central Maluku PHCs, which still needed to carry out special handling of drug storage LASA (Tualeka et al, 2021).…”
Section: Distribution and Storagementioning
confidence: 99%
See 3 more Smart Citations
“…Study at Tegal PHCs, reported that drug storage according to dosage form, temperature, and FEFO (First In, First Out) met the standard 100% (Cholilah et al, 2021). The percentage of the suitability of drug storage LASA (Look Alike Sound Alike) at Boja, Kendal PHCs was 50% (Yuswantina et al, 2022), Tegal PHCs was 87.5% (Cholilah et al, 2021) and South Kalimantan PHCs was 88% (Anisah et al, 2023). It was different at Central Maluku PHCs, which still needed to carry out special handling of drug storage LASA (Tualeka et al, 2021).…”
Section: Distribution and Storagementioning
confidence: 99%
“…Research at South Kalimantan PHCs showed that drug officers knowledge regarding proper drug storage procedures also influences the high value of defective and expired drugs was 17.37% (Rezeki et al, 2021). The drug storage according to dosage form and temperature was 97.56% due to drug officers not periodically controlling the temperature of the storage room (Anisah et al, 2023). Planning for human resource needs according to the workload of drug officers at PHCs was needed so that they could carry out drug management according to their competence (Carolien et al, 2017).…”
Section: Human Resourcesmentioning
confidence: 99%
See 2 more Smart Citations